Causality patterns between exchange rates and stock prices : evidence from daily data of eight East Asian countries. - Lau, Hon Wei. (2010)
The issue of exchange rate and stock price interactions has been postulated in theoretical models such as asset pricing models and portfolio balance models. Most of the empirical studies on asset pricing models and portfolio balance models utilized single-equation models to represent exchange rate and stock price interactions. However, it is important to note that the issue on exogeneity of the explanatory variables is critical in the efficient estimation of the parameters within a single-equation framework. The definition of exogeneity of the explanatory variables affects statistical inferences and more importantly, it influences the predictive power of the models. According to Engle, Hendry and Richard (1983), the exogeneity of the explanatory variables is dependent on their causality relationship with the endogenous variables. Therefore, this paper aims to study the causality patterns between the returns and volatility of exchange rates and stock prices.